2016
DOI: 10.1016/j.jtusci.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory activity of aldose reductase of flavonoid compounds: Combining DFT and QSAR calculations

Abstract: The DFT-B3LYP method, with the base set 6-31G (d), was used to calculate several quantum chemical descriptors of 44 substituted flavonoids. The best descriptors were selected to establish the quantitative structure activity relationship (QSAR) of the inhibitory activity against aldose reductase using principal components analysis (PCA), multiple regression analysis (MLR), nonlinear regression (RNLM) and an artificial neural network (ANN). We propose a quantitative model according to these analyses, and we inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Authors concluded that overall toxicity of the phenol derivatives involves a balance between electron density on the aromatic ring and lipophilicity. Also, electron withdrawing substituents induced toxicity, but much less than their electron donating counterparts (Selassie et al, 1998;Ghamali et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Authors concluded that overall toxicity of the phenol derivatives involves a balance between electron density on the aromatic ring and lipophilicity. Also, electron withdrawing substituents induced toxicity, but much less than their electron donating counterparts (Selassie et al, 1998;Ghamali et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…MLR can also be used to select descriptors to be used as input parameters in MNLR PLS and ANN. Multiple linear regression, partial least squares (PLS) and multiple non-linear regression models (MLR) were generated to predict anticancer activities and pIC50 [26][27][28][29] using the software XLSTAT (2015 version) [30] and the ANN was generated using the software Matlab.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are neither theoretical nor empirical rules to definitively determine the number of quiet layers or the number of neuron layers required to generate an optimal ANN, one hidden layer seems to be sufficient for most chemical applications of ANN. Some authors [27,32] have offered a parameter to be used to calculate the optimal number of hidden neurons, which plays a major role in determining the best ANN architecture. ρ is defined as follows: ρ = (Number of data points in the training set/ Sum of the number of connections in the ANN).…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis (PCA) [37] was conducted to identify the link among different variables. Table 3 presents the correlation matrix that represents the correlations among the fourteen descriptors.…”
Section: Principal Component Analysismentioning
confidence: 99%